U-shaped relationship between pre-operative plasma fibrinogen levels and severe peri-operative bleeding in cardiac surgery. Issue 10 (October 2020) - Mion, Stefano; Duval, Benoît; Besnard, Thibaut; Darné, Bernadette; Mouton, Christine; Jecker, Olivier; Labrousse, Louis; Remy, Alain; Zaouter, Cédrick; Ouattara, Alexandre
Abstract : BACKGROUND: An inverse linear relationship has been reported between pre-operative fibrinogen levels and postoperative blood loss in cardiac surgery. However, recently high pre-operative fibrinogen levels have also been reported to be associated with increased blood transfusion and re-operation. OBJECTIVE: We tested the hypothesis that the relationship between pre-operative fibrinogen levels and severe peri-operative bleeding is not linear. DESIGN: A large-scale ( n  = 3883) single-centre retrospective study. SETTING: A tertiary care teaching hospital. PATIENTS: We analysed data from our institutional database which includes all patients above 18 years who underwent on-pump cardiac surgery through a sternotomy between September 2010 and May 2014. MAIN OUTCOME MEASURES: Peri-operative severe bleeding adapted from the Universal Definition of Peri-operative Bleeding, class 3 or 4. The relationship between pre-operative fibrinogen levels and peri-operative severe bleeding was analysed by binary logistic regression. A cubic B-spline transformation was used to estimate the relationship between pre-operative fibrinogen level associated with excessive peri-operative bleeding. RESULTS: Severe peri-operative bleeding was observed in 957 (24.6%) patients. An L-shaped relationship was observed between pre-operative fibrinogen levels and 24-h postoperative blood loss. The relationship between pre-operative fibrinogen levels and severe peri-operative bleeding (i.e. Universal Definition of Peri-operative Bleeding class 3 or 4) was U-shaped: the risk of severe peri-operative bleeding bottomed at 3.3 g l −1 when the upward sloping curve started at 5.8 g l −1 with a steeper increase above 8.2 g l −1 . CONCLUSION: We reported a U-shaped relationship between severe peri-operative bleeding and pre-operative fibrinogen levels. While a low-level of fibrinogen appears to be associated with a high risk of bleeding, a high level does not necessarily protect the patient against such a risk and could even be a risk factor for peri-operative bleeding.